Effect of sulfiting on the quality of fresh coconut meat quarters - Intalan, Irma Wenceslao; Dumelod, Benelyn Domingo (1994.)
This study was undertaken with the main objective of determining the effectivity of sodium metabisulfite as a pre-treatment for fresh coconut meat. The shelf life of the untreated coconut meat and the optimum level of sodium metabisulfite to be used were determined in the preliminary study. Based on the assumption that the onset of deterioration was the presence of yellow-green molds on coconut meat, the shelf life of the untreated coconut meat was found to be two days and the optimum level to be 8% sodium metabisulfite solution. In the first phase, the effect of sulfiting on some microbiological, sensory and physico-chemical properties of fresh coconut meat was investigated. Results of the microbiological examination implied that treatment with 8% solution of sodium metabisulfite lengthened the shelf life of the coconut meat from two days to two weeks. Browning reactions and the development of rancid odor were prevented up to eight days of storage at room temperature. Results of rancidity tests showed that sulfiting was effective in controlling the development of fat rancidity in coconut meat. There was a minimal increase in peroxide value and free fatty acid content of the sulfited sample on storage. For the untreated sample, the PV and FFA content were 1.59 meq/kg and 0.41, respectively after two days of storage; while for the sulfited sample, 0.93 meq/kg and 0.28%, respectively after 14 days of storage at room temperature. Results of moisture content and sulfite residue analyses gave a decreasing trend. The final sulfite residue of the treated sample was within the allowable limit of 1,000 ppm. Aflatoxin content analysis revealed that treatment with 8% sodium metabisulfite solution was effective in controlling the production of aflatoxin in fresh coconut meat. In Phase II, the equilibrium moisture contents of the untreated and sulfited samples were determined using Proximity Equilibrium Cells (PECs). The resulting graph did not assume a typical sigmoidal curve. The use of other method which is applicable for samples with high initial moisture content like the fresh coconut meat was recommended.
Thesis (BSFT)--University of the Philippines Diliman.
Keywords: Coconut meat; Coconut meat -- Preservation